Relationship between hepatic and systemic angiopoietin‐like 3, hepatic Vitamin D receptor expression and NAFLD in obesity. (28th June 2020) - Barchetta, Ilaria; Cimini, Flavia A.; Chiappetta, Caterina; Bertoccini, Laura; Ceccarelli, Valentina; Capoccia, Danila; Gaggini, Melania; Di Cristofano, Claudio; Della Rocca, Carlo; Silecchia, Gianfranco; Leonetti, Frida; Lenzi, Andrea; et al.
Abstract: Background & Aims: Non‐alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide and an independent risk factor for cardiovascular mortality. Angiopoietin‐like proteins (ANGPTLs) are targets for vitamin D receptor (VDR)‐mediated gene transcription and this axis may promote NAFLD. ANGPTL3 is a hepatokine which inhibits lipoprotein lipase and its experimentally induced inactivation reduces hepatosteatosis. Little is known on ANGPTL3 in human NAFLD and no data exist on its relationship with hepatic VDR/VD‐related genes. The aim of this research was to investigate hepatic ANGPTLs and VDR/VD‐related gene expression in human obesity in relation to NAFLD. Methods: We conducted a cross‐sectional investigation on forty obese subjects with/without NAFLD. We evaluated hepatic ANGPTL3, ANGPTL4, ANGPTL8, LPL, VDR, CYP27A1 and CYP2R1 mRNA expression in liver biopsies by RT‐PCR; VDR expression was further investigated by immunohistochemistry; circulating ANGPTL3 was measured by Milliplex assay. Results: Compared to non‐NAFLD, NAFLD individuals had significantly higher hepatic VDR, ANGPTL3 and LPL expression. ANGPTL3 correlated with steatosis grade, LPL, VDR, CYP27A1 and CYP2R1 expression. Plasma ANGPTL3 concentrations were positively associated with clinical/histological markers of NAFLD/NASH and with hepatic ANGPTL3 expression. Greater hepatic VDR expression was the main determinant of hepatic ANGPTL3 after adjusting for multiple confounders. Conclusions: Hepatic ANGPTL3 expression correlates with greater VDR expression, presence and severity of NAFLD and translates in increased circulating ANGPTL3, likely as a result of its modulation by up‐regulated hepatic VDR in NAFLD. This study provides novel insights to potential mechanisms underlying ANGPTLs–mediated ectopic fat accumulation and NAFLD development in obesity.